NSUN5 accelerates the progression of liver hepatocellular carcinoma by m5C-EFNA3-mediated glycolysis - Yehong Han; Xueqin Deng; Haixia Chen; Jie Chen; Wei Xu; Lanqin Liu (BMC Cancer)
Abstract Background Aerobic glycolysis is a hallmark of cancers including liver hepatocellular carcinoma (LIHC). RNA m5C methylation is involved in LIHC progression. However, the effect of a m5C writer, NSUN5, on glycolysis in LIHC remains not known. The present study aimed to investigate the effect of NSUN5 on glycolysis in LIHC and the molecular mechanism. Methods NSUN5 and EFNA3 expression data were acquired from The Cancer Genome Atlas database. Cell viability and glycolysis were evaluated. Tumor growth was evaluated using the xenograft tumor model. The effect of NSUN5 on EFNA3 m5C methylation was evaluated using methylated RNA immunoprecipitation and dual-luciferase reporter assay. Results We found that NSUN5 and EFNA3 expression was increased in LIHC and related to poor survival. Knocking down NSUN5 inhibited LIHC cell viability and glycolysis in vitro, and inhibited tumor growth and glycolysis in vivo. Moreover, the expression of NSUN5 was positively correlated with that of EFNA3. NSUN5 stabilized EFNA3 by promoting m5C modification of EFNA3. Additionally, overexpression of EFNA3 reversed the inhibition of cell viability and glycolysis induced by NSUN5 silence. Conclusion Silencing of NSUN5 decelerates LIHC progression by inhibiting glycolysis mediated by EFNA3 with m5C modification, highlighting the potential of NSUN5 as a therapeutic target for LIHC.